DEVELOPMENT OF AN ADAPTIVE DIGITAL ECOSYSTEM MODEL TOWARDS A SUSTAINABLE SMART CITY IN BANYUWANGI REGENCY - Ismail Nurdin; Etin Indrayani; Eem Nurnawaty; Dedhy Guntoro; Ikra Novar Rizqi; M. Rahimi Hasan (Lembaga Riset dan Pengkajian Strategi Pemerintahan IPDN, 2026)
This research is conducted to create an adaptive and sustainable Smart City ecosystem model for Banyuwangi Regency in response to challenges of digitalization and sustainable development in the region. The study emphasizes three pillars: building digital infrastructure, improving stakeholder cooperation, and formulating regulations conducive to technological innovation. Employing an exploratory qualitative method, the research was conducted through 18 in-depth interviews, direct observation, document analysis, and FGDs with diverse stakeholders. The collected data were analyzed using a paradigmatic model to construct a